Ivan Mirchuk and Slavic philosophical congress in Warsaw (1927) - Ivanyk, Stepan (Sententiae, 2011)
For the first time in domestic literature the article describes the circumstances of par-ticipation of Ukrainian delegation in the Slavic philosophical congress in Warsaw (1927) and describes toe polemics around the presentation of Ivan Mirchuk.